Cultivating Open Science: a quantitative exploration of leadership practices in Malaysian academic libraries - Hazmir Zainal,; Siti Wahida Amanullah,; Shamsudin Ibrahim,; Hendon Abdullah, (Malaysian Journal of Library and Information Science, 2023)
This paper explores the characteristics of open leadership to support academic library leaders in promoting open science. It also aims to identify the existing leadership practices related to the implementation of open science from the viewpoint of Malaysian academic library leaders. The research employs a quantitative approach, utilizing online surveys distributed among 50 leaders from Malaysian public and private academic libraries. The study is anchored in the Open Leadership Framework, encompassing three key practices: design (contextualization), build (structure and system creation), and empower (personal leadership skills). Open leadership, viewed as a response to technological advancements and the use of multimedia communication tools, is framed within the principles, practices, and skills that communities can leverage to achieve shared goals. The findings from the design principle indicate unanimous agreement among respondents on the importance of collaboration, both internally and externally, for the success of the open science agenda, aligning with the principles of community interactions. In the build principle, all respondents share the belief that libraries should implement training and competence development programs, aligning with mentoring principles. This adherence corresponds to the principles of commons-based production, emphasizing the encouragement of publication in open-access journals, and project management, highlighting the pivotal role of libraries in determining the university's open data repository. In the empowerment principle, a total response of 61.5 percent under the "makes connection" principle, emphasizes the need for collaboration between the library, the university's Information Technology Center, and the Research Management Center to provide researcher profiles. This study not only provides insights into the current landscape of open leadership practices among Malaysian academic library leaders but also offers valuable implications for fostering collaboration, training initiatives, and empowerment strategies in the realm of open science. By understanding and embracing these principles, academic institutions and libraries can navigate the evolving scholarly environment, effectively contributing to the advancement of open science practices.